2008
DOI: 10.1007/s00421-008-0762-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recovery time on phosphocreatine kinetics during repeated bouts of heavy-intensity exercise

Abstract: The purpose of this study was to examine the kinetics of phosphocreatine (PCr) breakdown in repeated bouts of heavy-intensity exercise separated by three different durations of resting recovery. Healthy young adult male subjects (n = 7) performed three protocols involving two identical bouts of heavy-intensity dynamic plantar flexion exercise separated by 3, 6, and 15 min of rest. Muscle high-energy phosphates and intracellular acid-base status were measured using phosphorus-31 magnetic resonance spectroscopy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 46 publications
7
24
2
1
Order By: Relevance
“…The value for moderate exercise in the control condition of the present study (ϳ15 s) was somewhat smaller than we (32) and others (3,4,55) have reported previously (ϳ23-35 s) but similar to the values that have been considered to be realistic for moderate exercise (52). On the other hand, the value for heavy exercise in the control condition of the present study (ϳ55 s) was similar to or somewhat greater than we (29,30,32) and others (14,56,57) have reported previously (38 -54 s). The explanation for the substantial slowing of [PCr] kinetics between moderate-and heavy-intensity exercise in the present study and also in an earlier study from our laboratory (32) is obscure but might be related to our experimental protocol, which involves unilateral concentric/eccentric knee extension exercise, potentially resulting in high muscle tension development during high-intensity exercise and consequent impairments to muscle blood flow and oxygenation (30).…”
Section: Discussionsupporting
confidence: 86%
“…The value for moderate exercise in the control condition of the present study (ϳ15 s) was somewhat smaller than we (32) and others (3,4,55) have reported previously (ϳ23-35 s) but similar to the values that have been considered to be realistic for moderate exercise (52). On the other hand, the value for heavy exercise in the control condition of the present study (ϳ55 s) was similar to or somewhat greater than we (29,30,32) and others (14,56,57) have reported previously (38 -54 s). The explanation for the substantial slowing of [PCr] kinetics between moderate-and heavy-intensity exercise in the present study and also in an earlier study from our laboratory (32) is obscure but might be related to our experimental protocol, which involves unilateral concentric/eccentric knee extension exercise, potentially resulting in high muscle tension development during high-intensity exercise and consequent impairments to muscle blood flow and oxygenation (30).…”
Section: Discussionsupporting
confidence: 86%
“…This was similar to the effect of prior exercise on subsequent bouts of exercise reported previously (6,29,34). In the present study, for example, during the human high-intensity protocol there was a significant time effect (P ϭ 0.015) observed when comparing the lowest pH obtained during each repeated cycle, with the first cycle having a lower pH compared with the subsequent repeated bouts (cycle 1: pH 6.77 Ϯ 0.05; cycles 2-5: pH range 6.86 Ϯ 0.02 to 6.89 Ϯ 0.02).…”
Section: Preliminary Analysis Of Ph and Pcrsupporting
confidence: 90%
“…In this leg position the SOL muscle is expected to be involved more than the two gastrocnemii 20. This second examination was performed at least 20 min after the first one, to ensure sufficient metabolic recovery 36. Two additional spiral‐MRSI measurements were performed at rest in two of these subjects in order to acquire representative flip angle maps37 in both leg positions.…”
Section: Methodsmentioning
confidence: 99%